Greenhouse Gas Emissions and Biogas Potential from Livestock in Rural Indonesia - Heriyanti, A. P.; Purwanto, P.; Purnaweni, H.; Fariz, T. R. (Jurnal Pendidikan IPA Indonesia, 2022)
The livestock sector is one of the most significant contributors to greenhouse gas (GHG) emissions. Jetak Village in Indonesia has a large livestock population, so it has the potential to be a reasonably high contributor to GHG emissions. Therefore, research is needed to calculate GHG from the livestock sector and calculate biogas potential. Besides, we also discuss data collection techniques that are important but often forgotten in GHG reduction studies in developing countries. This is useful as an effort and reference to reduce GHG emissions in rural areas, especially in Jetak Village. The GHG calculation uses the Tier-1 method, while the data on the potential for biogas utilization is obtained from manure production calculations and in-depth interviews. The calculation results show that the highest total GHG from livestock management in Jetak Village in 2017 was 1,106.69 tons CO2-eq/year, while the lowest total GHG emissions in 2015 were 1,018.41 CO2-eq Gg/year. Dairy cows are the biggest emitter in livestock management, with 4,919.61 tons of CO2-eq/year, and laying hens are the lowest emitters with 1.39 tons CO2-eq/year. Dairy cows are the largest contributor to GHG emissions in enteric fermentation with 9,680.52 tons CO2-eq/year, and the lowest number of contributors is horses with 20.79 tons CO2-eq/year. The potential of biogas in Jetak Village based on manure production is 137 installations. The positive community's perception supports this. It tends to be less valid regarding livestock population data used for GHG calculations, so we verified it during in-depth interviews. The in-depth interview process used local language to enhance the quality of responses. This research needs to be developed considering our findings that there are only 50 biogas installations, indicating the biogas potential is not being utilized to its full potential.